COLORIMETRIC DETERMINATION OF PARACETAMOL IN RAW MATERIAL AND IN PHARMACEUTICAL DOSAGE FORMS (Biological Sciences - PJSIR, 2002)
A rapid , accurate and simple method is proposed for the determination of p-acetaminophen (paracetamol) in raw material, tablets and syrups. The method is based on measuring the i ntensity of the yellow color that developed when acute acetaminophen is allowed to react with p-dimethylaminobenzaldehyde in 2M I-IC! after heating.The color which absorbs in  the visible region  oft,450nm  is stable for several hours and the intensity is directly proportional  to the concentration of the drug, that is, Beer-lambert law is obeyed. The method can be used to analyse paracetamol in raw material  and in pharmaceutic al dosage forms.